The composition and vascular/antioxidant properties of Taraxacum officinale flower water syrup in a normal-fat diet using an obese rat model. (30th January 2021) - Majewski, Michał; Lis, Bernadetta; Juśkiewicz, Jerzy; Ognik, Katarzyna; Jedrejek, Dariusz; Stochmal, Anna; Olas, Beata
Abstract: Ethnopharmacological relevance: Taraxacum officinale (L.), commonly called dandelion has been used for centuries as a natural medicine to treat inflammatory diseases including some metabolic alterations associated with obesity. Aim of the study: Based on animal experiments this study aims to explore the potential mechanisms of action of T. officinale flower water syrup (TOFS) together with a normal-fat diet in the intervention of obesity. Materials and methods: Obese male albino-Wistar rats ( n  = 8) at 25 weeks of age were fed with a normal-fat diet with or without added 27.82% TOFS (w/w) for 4 weeks. The reactivity of thoracic aorta and antioxidant capacity were studied. Results: TOFS delivered daily 926.8 μg of L-chicoric acid, 20.19 μg of luteolin and 3.379 ‬g of sucrose. TOFS showed beneficial effects by regulating blood lipids (HDL, x1.11-fold increase), thereby lowering the risk factors for atherosclerosis (TC/HDL, x0.90-fold). The antioxidant status was improved via an increase in plasma superoxide radical scavenging (SOD, x1.6-fold) and a decrease in lipid peroxidation (MDA, x0.81-fold). Moreover, the following were decreased: Cu (x0.53-fold), Zn (x0.72-fold) and the Cu/Zn molar ratio (x0.60-fold). A marker for liver damage/disease was beneficially decreased (ALP, x0.87-fold). TOFS modulated in a significant way COX-depended relaxation to ACh ( p  = 0.05) but not to CORM-2 ( p  = 0.1651) in isolated thoracic arteries, by decreased participation of vasoconstrictor prostanoids. The vascular contraction to prostaglandin F2α was also decreased (x0.62-fold). We observed no change in the feed intake, body weight, organ-to-body weight ratio, blood glucose, CAT, FRAP, AST, ALT, TBARS/carbonyls (in heart, liver, kidneys, spleen) and carbonyls (in blood plasma, thoracic arteries); as well as F2 -isoprostanes in urine. Vascular response to the vasodilators ACh, SNP, A23187, CORM-2, pinacidil, NS-1619 and to the vasoconstrictors NA, U-46619, ET-1 as well as hyperpolarizing mechanism(s) were not modified. Conclusions: TOFS possesses beneficial properties by regulating prostanoids and antioxidant status. Highlights: T. officinale flower water syrup (TOFS) is a source of L-chicoric acid and luteolin. TOFS supplementation improves HDL-cholesterol in obese rats fed a normal-fat diet. TOFS increases SOD activity and decreases the Cu/Zn ratio, ALP and MDA in blood plasma. TOFS has a beneficial influence on COX-dependent ACh-induced vasodilation. The contraction to PGF2α is decreased in thoracic arteries of TOFS-fed rats. Graphical abstract: Image 1